Association of hoarding case identification and animal protection programs to socioeconomic indicators in a major metropolitan area of Brazil - de Moura, Raphael Rolim; de Castro, Wagner Antonio Chiba; Farinhas, João Henrique; da Cunha, Graziela Ribeiro; Pegoraro, Martha Maria de Oliveira; Kmetiuk, Louise Bach; dos Santos, Andrea Pires; Biondo, Alexander Welker (Frontiers in Veterinary Science, 2022)
The present study assessed the identification of animal and object hoarding disorder cases by contact and mapping and the presence of animal protection programs in association with seven social-economic indicators of the metropolitan area of the ninth-biggest metropolitan area of Brazil. City Secretaries of Health and Environment provided demographic information and responded to a questionnaire. Overall, a very high level of hoarding case identification per municipality was positively associated with a higher Human Development Index, population, density, and income and negatively associated with distance from Curitiba, the capital of Parana State. Low and very low levels of hoarding case identification were positively associated with a greater area, higher Social Vulnerability Index, inequality, illiteracy, and rural areas. Very high identification level of animal protection programs was also positively associated with higher HDI, density and population, urban area, and high income, and negatively associated with a geographical area. Similarly, low and very low levels of animal protection programs identification were positively associated with low income, illiteracy, and distance while negatively associated with higher population, urbanization, and higher HDI. In summary, better identification of hoarding cases and animal protection programs have shown a positive association with better socioeconomic indicators and higher population, density, and urban area. Whether municipalities with better human socioeconomic indicators may stimulate society's demands for identification of cases of individuals with hoarding disorder and animal programs should be further established. Regardless, animal health and welfare have been associated with improving human quality of life in a major Brazilian metropolitan area.